Chemical depth profiling and 3D reconstruction of III–V heterostructures selectively grown on non‐planar Si substrates by MOCVD. Issue 3 (23rd February 2015) - Gorbenko, V.; Veillerot, M.; Grenier, A.; Audoit, G.; Hourani, W.; Martinez, E.; Cipro, R.; Martin, M.; David, S.; Bao, X.; Bassani, F.; Baron, T.; et al.
Abstract : The chemical characterization of novel 3D architectures with nanometre‐scale dimensions is extremely challenging. The chemical composition of InGaAs/AlAs quantum wells selectively grown in SiO2 trenches, 100–300 nm wide, is studied. Combining high lateral resolution 3D ToF‐SIMS analysis and Auger measurements, the chemical composition of individual trenches was obtained confirming the uniformity of these III–V heterostructures. These results correlate well with an average approach using SIMS depth profiling. The effects of ion beam orientation on the surface topography of confined structures were highlighted. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : This work describes an innovative method for secondary ion mass spectrometry high depth profiling of 3D structures that are smaller than the lateral resolution of the instrument. The chemical composition of InGaAs/AlAs quantum wells selectively grown in SiO2 trenches, 100–300 nm wide, was studied. Combining 3D ToF‐SIMS analysis and Auger measurements, the chemical composition of individual trenches was obtained.